2019
DOI: 10.1136/bmjopen-2019-032182
|View full text |Cite
|
Sign up to set email alerts
|

Professionals’ perspectives on factors affecting GP trainees’ patient mix: results from an interview and focus group study among professionals working in Dutch general practice

Abstract: IntroductionSeeing and treating patients in daily practice forms the basis of general practitioner (GP) training. However, the types of patients seen by GP trainees do not always match trainees’ educational needs. Knowledge about factors that shape the mix of patient types is limited, especially with regard to the role of the professionals who work in the GP practice.AimWe investigated factors affecting the mix of patients seen by GP trainees from the perspective of professionals.Design and settingThis qualita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
(52 reference statements)
2
4
0
Order By: Relevance
“…Clinical experiences gained during progressively independent practice were perceived by residents as the cornerstones of their PIF. This is in line with earlier studies on PIF in UGME,21 43 which revealed the importance of experience gained from direct encounters with patients; it also echoes what is known about how residents learn 44–46. Our findings about residents’ learning on the job and from the job, and their move to full participation, provide empirical evidence for what has been theorised on PIF previously 9 11 12 36.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Clinical experiences gained during progressively independent practice were perceived by residents as the cornerstones of their PIF. This is in line with earlier studies on PIF in UGME,21 43 which revealed the importance of experience gained from direct encounters with patients; it also echoes what is known about how residents learn 44–46. Our findings about residents’ learning on the job and from the job, and their move to full participation, provide empirical evidence for what has been theorised on PIF previously 9 11 12 36.…”
Section: Discussionsupporting
confidence: 91%
“…This is in line with earlier studies on PIF in UGME, 21 43 which revealed the importance of experience gained from direct encounters with patients; it also echoes what is known about how residents learn. [44][45][46] Our findings about residents' learning on the job and from the job, and their move to full participation, provide empirical evidence for what has been theorised on PIF previously. 9 11 12 36 It supports the assertion that PIF is most effectively influenced through 'situations, not subjects', that is, that residents' professional identity is more likely to be influenced by doing the work than by being taught about it.…”
Section: It All Happens In the Workplacesupporting
confidence: 71%
“…Moreover, another study by our research group investigating the view of professionals on trainees' patient mix indicated that trainees could become the preferred doctor of patients with long-term conditions. Repeated visits and the trainee's behaviour were important in establishing the relationship [16] The influence of trust on patients' willingness to see a trainee is another important finding. Patients needed to trust trainees before they would consider consulting with them.…”
Section: Discussionmentioning
confidence: 99%
“…Other topics were the influence of the complexity of a condition, prior experiences with trainees, knowledge about a trainee and the impact of the characteristics of a trainee (like gender or age) on a patient's decision to consult the trainee. The topic list was based on findings from our earlier study on the perspectives of professionals working in general practice [16], additional literature [14,[17][18][19] and discussions within the research team. The topic list can be found in Appendix I.…”
Section: Data Collectionmentioning
confidence: 99%
“…3 However, other members of the healthcare team also have an active role in this. Proposing learning opportunities has been documented as an activity of medical receptionists, 16 advanced practice professionals 16,17 and nurses. 4 On the flipside, healthcare team members can also actively withhold learning opportunities from trainees.…”
Section: Orchard Accessibility: Getting Learning Opportunitiesmentioning
confidence: 99%